Hallazgos de aves poco comunes en el norte argentino - Narosky, Samuel (1988)
New records for Crypturellus undulotus in Formosa, Argentina and for Tryngites subruficollis and Metriopelia cecilioe in Jujuy, Argentina are commented. Previous records for these species in northern Argentina are very few.